Group identification and giving: in-group love, out-group hate and their crowding out - Shaun P. Hargreaves Heap; Eugenio Levi; Abhijit Ramalingam (Masaryk University, Faculty of Economics and Administration, 2021)
Using a dictator game experiment, we examine whether the introduction of group identities affects giving. Group identities can activate feelings of in-group love and out-group hate to create an in-group bias. In addition, group identities may spawn social sanctions that are designed to reinforce this in-group bias. We find that the aggregate effect on giving of group identities alone tends to be positive but depends on the relative size of two sub-sets of the subject pool: those who exhibit an in-group bias and those who do not. With the latter, the introduction of group identities has no effect on giving. With the former, the in-group bias arises from both in-group love and out-group hate and with interactions skewed towards own group members, in-group love will dominate to produce an increase in gifts. Sanctions too depend for their aggregate effect on the relative size of these two sub-sets in the population, but in the opposite way. This is because in-group biased preferences are crowded-in by the sanctions among the hitherto equal givers and in-group biased preferences are crowded-out among those who would otherwise exhibit the in-group bias.
Keywords: C72; C91; D31; D63; D91; J70; Z18; 330; dictator game; in-group love; out-group hate; crowding-out